2015
DOI: 10.3920/bm2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synbiotic on anthropometry, lipid profile and oxidative stress in obese children

Abstract: Recent studies have suggested some beneficial effects of probiotics and/or prebiotics on obesity in adults; such experience is limited in children and adolescents. This study was an open-label, randomised, controlled study including children with primary obesity. The first group was treated with a standard method with a reduced calorie intake and increased physical activity. The second group received add-on daily synbiotic supplementation during one month. The aim of this study was to evaluate potential effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 27 publications
0
48
1
1
Order By: Relevance
“…Safavi et al (27) showed a significant difference in all lipid parameters after 8 weeks of synbiotic supplementation in obese children. In contrast, Ipar et al (28) found significant improvement only in TC and LDL levels and not in TG levels after synbiotic supplementation, as in our study. Effects of probiotics or synbiotics on TG levels have some controversies; Gao et al (26) revealed that lipid-lowering effect of probiotics or synbiotics may vary in different countries/ethnicities.…”
Section: Discussioncontrasting
confidence: 55%
“…Safavi et al (27) showed a significant difference in all lipid parameters after 8 weeks of synbiotic supplementation in obese children. In contrast, Ipar et al (28) found significant improvement only in TC and LDL levels and not in TG levels after synbiotic supplementation, as in our study. Effects of probiotics or synbiotics on TG levels have some controversies; Gao et al (26) revealed that lipid-lowering effect of probiotics or synbiotics may vary in different countries/ethnicities.…”
Section: Discussioncontrasting
confidence: 55%
“…These 12 articles included a total of 767 samples, with 391 treatments and 376 controls. [25][26][27][28][29][30][31][32][33][34][35][36] The detailed results are shown in Table 1 and Table S1. † Five of these studies were conducted in Asia, [25][26][27]29,30 five were conducted in Europe, 28,[31][32][33]36 one in Oceania, 35 and one in America.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36] The detailed results are shown in Table 1 and Table S1. † Five of these studies were conducted in Asia, [25][26][27]29,30 five were conducted in Europe, 28,[31][32][33]36 one in Oceania, 35 and one in America. 34 The subjects were adults in seven papers, [25][26][27][28][34][35][36] children or adolescents in three papers, [29][30][31] and women in two papers.…”
Section: Resultsmentioning
confidence: 99%
“…Ein günstiger Effekt von mehreren Bakterienstämmen (Lactobacillen und Bifidobakterien) in Kombination mit Fructooligosacchariden auf den BMI-Z-Score und den Bauchumfang ("Synbiotikum") wurde außerdem in einer doppelblinden randomisierten [32] bzw. einer offen randomisierten Studie an Kindern mit Adipositas berichtet [15].…”
Section: Bakterielle Metaboliten Und Adipositasunclassified